Comparison of Thrombocyte Indices and Immature Platelet between Preeclampsia and Normal Pregnancy - Chakrawati Hayuningsih; Leni Lismayanti; Anna Tjandrawati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
The primary pathophysiology of preeclampsia is abnormal trophoblast invasion, vasospasm, and endothelial dysfunction occurring, as well as platelet activation, increased platelet consumption, and the stimulation of the release of new platelets, which affects the platelet indices and immature platelets. This study compared the platelet indices (Mean Platelet Volume=MPV, Platelets Distribution Width=PDW, Platelet Large Cell Ratio=PLCR, and Immature Platelet Fraction (IPF) between preeclampsia and normal pregnancy. This research was an unpaired comparative analytic observational study with a cross-sectional design conducted in the Tangerang District General Hospital from February to August 2020. The platelet indices (MPV, PDW, PLCR) and IPF of preeclampsia subjects (n=33) at Tangerang District General Hospital and normal pregnant subjects (n=38) at Annisa Hospital Tangerang were examined using the Sysmex XN-1000 automatic hematology analyzer. Comparative platelet indices and IPF analysis were carried out by independent T-test or Man-Whitney test. Receiver Operating Characteristics (ROC) analysis was performed to obtain the cut-off value of the platelet indices and IPF to differentiate preeclampsia and normal pregnancy. The platelet indices and IPF were significantly higher in preeclampsia. The mean (SD) MPV was 10.86 (0.9) fL and 10. (0.89) fL, p<0.001; PDW 12.7 (8.7-19.1) fL and 10.85 (8.5-15.7) fL, p<0.001; PLCR 31.96 (7.02) % and 25.06 (6.92) %, p<0.001; and IPF 8.50 (3.10-20.40)% and 2.75 (1.2-9.4)%, p<0.001, respectively in preeclampsia and normal pregnancy. ROC analysis showed that an IPF with an AUC of 0.88 (95% confidence interval (CI) 0.78-0.95) with an IPF cut-off value of >6.5% was a good marker, while the MPV cut-off >10.2 fL, AUC 0.75(95% CI 0.63-0.84), PDW cut-off >11.3fL, AUC 0.77 (95%CI 0.65-0.86) and PLCR cut-off >26.1%, AUC 0.76 (95% CI 0.65-0.85) were good enough markers to differentiate preeclampsia from normal pregnancy. Platelet indices and IPF were statistically significantly higher in preeclampsia. The IPF parameter is a good marker, while the platelet indices can be a pretty good marker to distinguish preeclampsia and normal pregnancy. The IPF parameter and platelet indices can be proposed as a routine examination in pregnancy. Changes in IPF and platelet indices can be early signs of preeclampsia or the development of preeclampsia.